Interactions between buprenorphine and antiretrovirals. II. The protease inhibitors nelfinavir, lopinavir/ritonavir, and ritonavir. - McCance-Katz, Elinore F; Moody, David E; Smith, Patrick F; Morse, Gene D; Friedland, Gerald; Pade, Patricia; Baker, Jennifer; Alvanzo, Anika; Jatlow, Peter; Rainey, Petrie M (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2006)
We examined drug interactions between buprenorphine, an opioid partial agonist available by prescription for treatment of opioid dependence, and the protease inhibitors (PIs) nelfinavir (NFV), ritonavir (RTV), and lopinavir/ritonavir (LPV/R). Opioid-dependent, buprenorphine/naloxone-maintained, human immunodeficiency virus (HIV)-negative volunteers (n=10 per PI) participated in 24-h pharmacokinetic studies, before and after administration of each PI. Symptoms of opiate withdrawal and excess were determined before and after PI administration. PI pharmacokinetics were determined and compared between opiate-dependent participants and healthy control participants (n=15 per PI). Administration of RTV, but not of NFV or LPV/R, resulted in a significant increase in the buprenorphine area under the concentration-time curve (AUC). Symptoms of opiate excess, however, were not observed. Buprenorphine had no significant effects on PI AUC. Adjustments of doses of either buprenorphine or NFV, LPV/R, or RTV are not likely to be necessary when these drugs are administered for the treatment of opioid dependence and HIV disease.
Keywords: Adult; Buprenorphine; Case-Control Studies; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Drug Interactions; Female; HIV Protease Inhibitors; HIV Seronegativity; Humans; Lopinavir; Male; Narcotic Antagonists; Nelfinavir; Opioid-Related Disorders; Probability; Pyrimidinones; Reference Values; Risk Assessment; Ritonavir